2020
DOI: 10.3390/cryst11010015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Metal Organic Frameworks by Ball-Milling

Abstract: Metal-organic frameworks (MOFs) have been used in adsorption, separation, catalysis, sensing, photo/electro/magnetics, and biomedical fields because of their unique periodic pore structure and excellent properties and have become a hot research topic in recent years. Ball milling is a method of small pollution, short time-consumption, and large-scale synthesis of MOFs. In recent years, many important advances have been made. In this paper, the influencing factors of MOFs synthesized by grinding were reviewed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 107 publications
(140 reference statements)
0
32
0
Order By: Relevance
“…230,231 While many classical solvent-based syntheses require expensive starting materials or catalysts, 232,233 mechanochemistry obviates the need for solubilising groups and allows one to avoid low DPs due to the rapid precipitation of products. 234 The need to reduce solvent waste has inspired several studies on the general mechanochemical synthesis of porous materials 235,236 such as porous carbons, [237][238][239][240][241][242][243][244][245][246][247][248] porous coordination polymers 249,250 (e.g., metal-organic frameworks (MOFs) [251][252][253][254][255] ), and purely organic polymers. 53,102,[256][257][258][259][260] Up to now, porous polymers have been exclusively synthesised by step-growth polymerisation, while particularly using polycondensation reactions.…”
Section: Mechanochemical Synthesis Of Porous Polymersmentioning
confidence: 99%
“…230,231 While many classical solvent-based syntheses require expensive starting materials or catalysts, 232,233 mechanochemistry obviates the need for solubilising groups and allows one to avoid low DPs due to the rapid precipitation of products. 234 The need to reduce solvent waste has inspired several studies on the general mechanochemical synthesis of porous materials 235,236 such as porous carbons, [237][238][239][240][241][242][243][244][245][246][247][248] porous coordination polymers 249,250 (e.g., metal-organic frameworks (MOFs) [251][252][253][254][255] ), and purely organic polymers. 53,102,[256][257][258][259][260] Up to now, porous polymers have been exclusively synthesised by step-growth polymerisation, while particularly using polycondensation reactions.…”
Section: Mechanochemical Synthesis Of Porous Polymersmentioning
confidence: 99%
“…While porous materials can be classified regarding their pore sizes as macroporous (pore sizes of >50 nm), as mesoporous (pore sizes of 2–50 nm) or as microporous (pore sizes of <2 nm), the term furthermore includes a variety of different material classes, such as zeolites, carbons or porous metal oxides 14–25 . Among them, another interesting subcategory are porous polymers, as for instance porous coordination polymers (PCPs), such as metal organic frameworks (MOFs), or porous organic polymers (POPs), which combine the advanced properties of polymers and of porous materials 26–33 . Especially POPs gain increasing attention, as they are not only characterized by high surface areas and unique pore geometries, but also by a beneficial thermal and chemical stability 34–36 …”
Section: Introductionmentioning
confidence: 99%
“…A small number of liquid solvents such as ethanol and water could enhance the molecules' mobility and increase the reactant activity, thus promoting a faster reaction. A study also reported that water crystals as an auxiliary solvent in mechanochemical synthesis could improve crystallinity (Tao and Wang 2021).…”
Section: Mechanochemical Synthesismentioning
confidence: 98%